The Influence of Managerial Ownership and Institutional Ownership on Agency Costs (Studies on Manufacturing Companies in The basic Industrial and Chemical Sectors Listed on The Indonesia Stock Exchange) - Ramon Arthur Ferry Tumiwa; Nova Christian Mamuaya (AIBPM Publisher, 2018)
The purpose of this study is to examine and analyze: (1) the effect of managerial ownership on agency costs, (2) the effect of institutional ownership on agency costs. and (3) the effect of managerial ownership and institutional ownership simultaneously against agency costs. This research was conducted at the basic industrial and chemical sectors of manufacturing companies listed on the Indonesia Stock Exchange 20142016. The companies analyzed amounted to 18 companies determined based on sampling criteria. The analysis method used is panel data analysis by using EViews 9 programming computer. The results of this study found that managerial ownership has an insignificant relationship with agency cost. The Institutional ownership has an insignificant with agency costs. The managerial ownership and institutional ownership have no significant effect on agency costs, simultaneous. Keywords: agency cost, managerial ownership, institutional ownership. manufacturing companies